VERBAL AND NUMERICAL APTITUDE OF GRADUATE NURSING STUDENTS AT ENTRY LEVEL7 - Andrade, Maxie; George, Anice; Mayya, Shreemathi; Furtado, Renee (European Scientific Journal, ESJ, 2013)
Nurses apply numerical skills for various functions e.g. drug/fluid calculations, estimation of traction weight, nutritional requirement estimations, estimation of incidence and prevalence in epidemiological surveys etc. Nurses are involved in emergency care and handle a variety of written and verbal orders in relation to patient care by health care providers. Thus computational and vocabulary skills are very essential for nurses. This article presents the entry level verbal and arithmatic abilities of Indian graduate nursing students.